HEART DIASTOLE (physiology, changes in pathological conditions) - Коvalenko, V.N.; Yabluchansky, M.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
There is systematically described left ventricle is (LV) diastole in physiological and pathological conditions. Diastole is considered as a key process in heart biomechanics, which forms a systole and whole cyclic activity of blood circulation. Concentration on diastolic function, early and proved interventions during diastolic dysfunction  are important components of cardiac insufficiency secondary prophylaxis and its effective treatment.